Modified ethyl cellulose emulsion, preparation method thereof and application of modified ethyl cellulose emulsion in degradable coated controlled-release fertilizer
By modifying ethyl cellulose emulsion, combined with triethyl citrate and nanotitanium dioxide, biodegradable envelope controlled-release fertilizer was prepared, which solved the problems of slow degradation of existing petroleum-based polymer envelope fertilizers and low fertilizer application efficiency, achieving more efficient fertilizer utilization and lower environmental pollution.
Patent Information
- Application Number
- CN202411965966.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
The current petroleum-based polymer-encapsulated fertilizer has an extremely low degradation rate in the natural environment, resulting in long-term accumulation poses a threat to the ecosystem. At the same time, the application efficiency of chemical fertilizers is low, resulting in rapid nutrient release and environmental pollution.
Biodegradable envelope controlled release fertilizer was prepared by physically blending ethyl cellulose with triethyl citrate and nanotitanium dioxide.
The modified ethyl cellulose emulsion improves the flexibility and hydrophobicity of the envelope, extends the nutrient release period, improves the utilization efficiency of fertilizers, reduces environmental pollution, and the membrane materials can be biodegradable and will not cause long-term harm to the environment.
Smart Images

Figure CN119875273A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of controlled-release fertilizer manufacturing, and in particular to a modified ethyl cellulose emulsion and a preparation method thereof, and application of the modified ethyl cellulose emulsion in degradable coated controlled-release fertilizers. Background Art
[0002] In recent years, with the continuous increase in my country's population, people's demand for food is also gradually increasing. At the same time, my country is also facing the problem of difficulty in increasing the area of arable land. In order to solve these two problems at the same time, the large-scale application of chemical fertilizers has become inevitable. However, after the chemical fertilizers are applied to the soil, their easy solubility will lead to the rapid release of nutrients. The nutrients that crops can absorb in a short period of time are limited, causing some fertilizer nutrients to be lost in gaseous form or lost with water. This phenomenon will lead to economic losses on the one hand, and increase environmental pressure on the other hand: causing groundwater pollution, eutrophication of water bodies and a series of other environmental problems. Therefore, improving the efficiency of fertilizer utilization, reducing its pollution to the ecological environment, and developing sustainable agriculture have become topics of concern to the world.
[0003] The development of polymer-coated controlled-release fertilizers is of great strategic significance for achieving the goal of reducing fertilizer use and increasing efficiency and achieving zero fertilizer growth. However, most of the existing coating polymers are petroleum-based polymers, such as polyurethane, alkyd resin, polyolefin, polyacrylate, etc. Due to their excellent hydrophobic properties, the controlled-release period of coated fertilizers prepared with them can be as long as 3 to 6 months. However, the structural characteristics of these materials make their degradation rate in the natural environment extremely low, and long-term accumulation in the environment poses a threat to the ecosystem. Therefore, there is an urgent need to develop biodegradable polymer-coated controlled-release fertilizers.
[0004] Ethyl cellulose (EC) is a kind of cellulose in which the hydroxyl groups on the main chain are partially replaced by ethyl groups through an etherification reaction. It is completely non-toxic to the human body and is often used in the fields of medicine and food. Ethyl cellulose is relatively more hydrophobic than other natural materials. The water contact angle of different ethyl celluloses is between 60 and 100°, while the water contact angle of other degradable materials, such as starch, is only 10 to 30°. Therefore, the controlled release period of the coated fertilizer prepared with it can reach about 1 to 7 days, and the controlled release period of the degradable coated fertilizer prepared with starch materials is generally shorter than 2 days. It can be seen that the characteristics of ethyl cellulose make it have great potential in the coating of slow-release fertilizers. However, the controlled release performance of ethyl cellulose coated fertilizers is still not long enough, and it needs to be modified to further extend the controlled release period of coated fertilizers. In addition, due to the rigid molecular structure of ethyl cellulose and the hydrogen bonding force of hydroxyl groups, it is not tough enough when used as a membrane material, and it shows obvious brittleness at room temperature.
[0005] Studies have shown that when the plasticizer triethyl citrate (TEC) is inserted into the polymer molecular chain, it can weaken the attraction between the chains, thereby reducing the glass transition temperature of the polymer and increasing its flexibility. The introduction of nano-sized oxide particles into ethyl cellulose to prepare composite films can effectively increase the hydrophobic angle of the composite film and reduce the water vapor permeability coefficient. In this study, plasticizer triethyl citrate and nano-titanium dioxide were used to modify ethyl cellulose by physical blending, aiming to improve the flexibility and hydrophobicity of ethyl cellulose, thereby improving the nutrient release characteristics of the coated fertilizer prepared with it. Summary of the invention
[0006] Technical problem to be solved: In view of the above-mentioned prior art, the present invention provides a modified ethyl cellulose emulsion and a preparation method thereof and application thereof in a degradable coated controlled-release fertilizer.
[0007] Technical solution: A modified ethyl cellulose emulsion, comprising, by mass, 10-30 parts of ethyl cellulose, 50-150 parts of ethanol, 1-5 parts of triethyl citrate, and 1-10 parts of nano-titanium dioxide ethanol dispersion, wherein the mass ratio of nano-titanium dioxide to ethyl cellulose does not exceed 25%.
[0008] Preferably, in terms of mass ratio, the emulsion is composed of 60 g of ethyl cellulose, 300 g of anhydrous ethanol, 6 g of triethyl citrate, and 15 g of nano-titanium oxide ethanol dispersion, of which the nano-titanium oxide is 3 g.
[0009] The ethoxy group (-OC2H5) in the ethyl cellulose is 44.0%-51.0%, the viscosity is 7-10cp, the metal oxide is titanium oxide, the average particle size of the nano titanium oxide ethanol dispersion is 15nm, and the titanium dioxide content is ≥20wt.%.
[0010] The preparation method of the modified ethyl cellulose emulsion comprises the following steps: placing ethyl cellulose, ethanol, triethyl citrate and nano-titanium dioxide ethanol dispersion in a reaction container, stirring and mixing at 65-75° C. to obtain a modified ethyl cellulose emulsion product.
[0011] Application of the modified ethyl cellulose emulsion in preparing biodegradable controlled-release coated fertilizer.
[0012] The application method is as follows: pouring the fertilizer core particles into a fluidized bed for preheating at 42-45° C., adding modified ethyl cellulose emulsion into a peristaltic pump, and spraying the modified ethyl cellulose emulsion onto the surface of the fertilizer core particles; after the spraying is completed, solidifying, drying, and cooling the product to obtain the coated controlled-release fertilizer, wherein the mass of the modified ethyl cellulose emulsion film layer is 1-15% of the mass of the fertilizer core particles, and the particle size of the controlled-release coated fertilizer core is 3-6 mm.
[0013] The application method is that the fertilizer core particles are urea particles, potassium chloride particles or compound fertilizer particles, the preheating time is 15 minutes, the speed of the peristaltic pump is 3-6rpm, and the spraying pressure is set to 0.2-0.4MPa.
[0014] The application method includes the steps of screening and dust removal of fertilizer core particles before spraying the modified ethyl cellulose emulsion to ensure the uniformity and quality of the coated fertilizer.
[0015] The application method is that the curing and drying process adopts a method of gradually increasing the temperature to promote the cross-linking and curing of the emulsion, thereby further enhancing the controlled release effect of the coated fertilizer.
[0016] Beneficial effects: The controlled-release coated fertilizer of the present invention is composed of fertilizer core particles and a modified ethyl cellulose film layer, and the raw materials of the modified ethyl cellulose film layer are ethyl cellulose, triethyl citrate and nano metal oxides. Compared with ethyl cellulose, the modification measures can effectively reduce the glass transition temperature of the coating, improve the flexibility of the coating material and slow down the nutrient release rate of the coated fertilizer, thereby improving the utilization efficiency of the fertilizer and slowing down the nutrient loss. The raw materials of the film material used in the present invention are widely available and can be degraded in the soil, with low production costs and no accumulation of film materials after long-term use of the fertilizer; the final products of degradation are carbon dioxide and water, and long-term use will not cause any adverse effects on the environment. The present invention adds a plasticizer to the ethyl cellulose substrate to improve the flexibility of the film material, and adds nano oxides to enhance the hydrophobic properties of the film material; the controlled release of the fertilizer is achieved through the application of new materials and reasonable proportions, which can not only effectively slow down the release rate of nutrients to the outside world, but also the used film material can be biodegraded, and the degradation products have no secondary pollution to the soil. The present invention combines the degradation of membrane materials with the controlled release process, which not only realizes the effective utilization of fertilizers, but also realizes the greening of membrane materials, which is of great significance to the sustainable development of agriculture. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Effect of coating amount on nutrient release characteristics of coated fertilizers.
[0018] Figure 2 Effect of coating material formulation on nutrient release characteristics of coated fertilizers. DETAILED DESCRIPTION
[0019] The test materials used in the embodiments of the present invention that are not specifically described are all conventional test materials in the art and can be purchased through commercial channels. The ethyl cellulose used in the present invention is model M9, CAS number 9004-57-3, purchased from Sinopharm Group; triethyl citrate CAS number 77-93-0, purchased from Sinopharm Group; nano silicon oxide ethanol solution model JL-SiO2-15C, solid content of 20%, particle size of 15nm, purchased from Beijing Dekedaojin Technology Co., Ltd.; nano titanium oxide ethanol solution model JL-TiO2-TA15, solid content of 20%, particle size of 15nm, purchased from Beijing Dekedaojin Technology Co., Ltd.
[0020] Example 1: Preparation of controlled-release coated fertilizer with 5% coating amount
[0021] 60g of ethyl cellulose, 300g of anhydrous ethanol, 6g of triethyl citrate accounting for 10wt.% of ethyl cellulose, and 15g of nano titanium dioxide ethanol dispersion (3g of nano titanium dioxide) are placed in a reactor, mixed with a stirring rod at a speed of 800rpm, and heated to 70°C, stirred for 2h and then left to stand for 2h to obtain a modified ethyl cellulose emulsion product; 500g of urea granules (particle size 4mm) are poured into a fluidized bed for preheating for 15min, 145g of the modified ethyl cellulose emulsion product is added to a peristaltic pump, and the modified ethyl cellulose emulsion is evenly sprayed on the surface of the fertilizer core particles to obtain a green and degradable coated controlled release fertilizer, in which the coating material accounts for 5% of the weight of the fertilizer core particles, and the solvent anhydrous ethanol is continuously used after condensation recovery. The operating parameters of the fluidized bed are: fertilizer preheating temperature: 42-45°C; nozzle atomization pressure: 0.2-0.4Mpa.
[0022] Example 2: Preparation of controlled-release coated fertilizer with 10% coating amount
[0023] 60g of ethyl cellulose, 300g of anhydrous ethanol, 6g of triethyl citrate accounting for 10wt.% of ethyl cellulose, and 15g of nano titanium dioxide ethanol dispersion (3g of nano titanium dioxide) are placed in a reactor, mixed with a stirring rod at a speed of 800rpm, and heated to 70°C, stirred for 2h and then left to stand for 2h to obtain a modified ethyl cellulose emulsion product; 500g of urea granules (particle size 4mm) are poured into a fluidized bed for preheating for 15min, 290g of the modified ethyl cellulose emulsion product is added to a peristaltic pump, and the modified ethyl cellulose emulsion is evenly sprayed on the surface of the fertilizer core particles to obtain a green and degradable coated controlled release fertilizer, in which the coating material accounts for 10% of the weight of the fertilizer core particles, and the solvent anhydrous ethanol is continuously used after condensation recovery. The operating parameters of the fluidized bed are: fertilizer preheating temperature: 42-45°C; nozzle atomization pressure: 0.2-0.4Mpa.
[0024] Example 3: Preparation of controlled-release coated fertilizer with 15% coating amount
[0025] 60g of ethyl cellulose, 300g of anhydrous ethanol, 6g of triethyl citrate accounting for 10wt.% of ethyl cellulose, and 15g of nano titanium dioxide ethanol dispersion (3g of nano titanium dioxide) are placed in a reactor, mixed with a stirring rod at a speed of 800rpm, and heated to 70°C, stirred for 2h and then left to stand for 2h to obtain a modified ethyl cellulose emulsion product; 500g of urea granules (particle size 4mm) are poured into a fluidized bed for preheating for 15min, 435g of the modified ethyl cellulose emulsion product is added to a peristaltic pump, and the modified ethyl cellulose emulsion is evenly sprayed on the surface of the fertilizer core particles to obtain a green and degradable coated controlled release fertilizer, in which the coating material accounts for 15% of the weight of the fertilizer core particles, and the solvent anhydrous ethanol is continuously used after condensation recovery. The operating parameters of the fluidized bed are: fertilizer preheating temperature: 42-45°C; nozzle atomization pressure: 0.2-0.4Mpa.
[0026] Comparative Example 1
[0027] Put 60g of ethyl cellulose and 300g of anhydrous ethanol in a reactor, mix them with a stirring rod at a speed of 800rpm, heat them to 70℃, stir them for 2h and then let them stand for 2h to obtain the finished ethyl cellulose solution; pour 500g of fertilizer core particles (particle size 4mm) into a fluidized bed for preheating for 15min, add 300g of the finished ethyl cellulose solution into a peristaltic pump, and evenly spray the ethyl cellulose emulsion onto the surface of the fertilizer core particles to obtain a green and degradable coated controlled release fertilizer, in which the coating material accounts for 10% of the weight of the fertilizer core particles, and the solvent anhydrous ethanol is used again after condensation recovery. The operating parameters of the fluidized bed are: fertilizer preheating temperature: 42-45℃; nozzle atomization pressure: 0.2-0.4Mpa.
[0028] Comparative Example 2
[0029] 60g of ethyl cellulose, 300g of anhydrous ethanol and 6g of triethyl citrate accounting for 10wt.% of ethyl cellulose are placed in a reactor, mixed with a stirring rod at a speed of 800rpm, and heated to 70°C, stirred for 2h and then left to stand for 2h to obtain a modified ethyl cellulose emulsion product; 500g of fertilizer core particles (particle size 4mm) are poured into a fluidized bed for preheating for 15min, 305g of the modified ethyl cellulose emulsion product is added to a peristaltic pump, and the modified ethyl cellulose emulsion is evenly sprayed on the surface of the fertilizer core particles to obtain a green and degradable coated controlled release fertilizer, in which the coating material accounts for 10% of the weight of the fertilizer core particles, and the solvent anhydrous ethanol is used continuously after condensation recovery. The operating parameters of the fluidized bed are: fertilizer preheating temperature: 42-45°C; nozzle atomization pressure: 0.2-0.4Mpa.
[0030] Comparative Example 3
[0031] 60g of ethyl cellulose, 300g of anhydrous ethanol and 15g of nano titanium dioxide ethanol dispersion (3g of nano titanium dioxide) are placed in a reactor, mixed with a stirring rod at a speed of 800rpm, and heated to 70°C, stirred for 2h and then allowed to stand for 2h to obtain a modified ethyl cellulose emulsion product; 500g of fertilizer core particles (particle size 4mm) are poured into a fluidized bed for preheating for 15min, 313g of the modified ethyl cellulose emulsion product is added to a peristaltic pump, and the modified ethyl cellulose emulsion is evenly sprayed on the surface of the fertilizer core particles to obtain a green and degradable coated controlled release fertilizer, in which the coating material accounts for 10% of the weight of the fertilizer core particles, and the solvent anhydrous ethanol is used again after condensation recovery. The operating parameters of the fluidized bed are: fertilizer preheating temperature: 42-45°C; nozzle atomization pressure: 0.2-0.4Mpa.
[0032] Test Example 1: Mechanical properties test
[0033] The coating materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to mechanical property test experiments. Emulsions were prepared according to the preparation steps of ethyl cellulose emulsions in Examples 1 to 3 and Comparative Examples 1 to 3, respectively, poured into a mold, placed in an oven at 50°C for drying for 1 day, and after all the solvents evaporated, a dumbbell-shaped product was obtained. A computer-controlled electronic universal testing machine was used to perform mechanical tests on the composite material. The data are shown in Table 1:
[0034] Table 1 Comparison of mechanical properties of materials
[0035]
[0036] As can be seen from Table 1, the membranes made according to the ratios of Examples 1 to 3 have lower tensile strength, higher elongation at break and lower elastic modulus than those of Comparative Examples 1 and 3, indicating that the strength of the membranes has been reduced and the flexibility has been improved, making processing easier. The membranes made according to the ratios of Examples 1 to 3 have no significant improvement in coating strength compared to Comparative Example 2, so the ratio of ethyl cellulose: triethyl citrate: nano titanium oxide = 20:2:1 for the coating material achieves a balance between toughness and strength, which is the optimal ratio for the coating material.
[0037] Test Example 2: Hydrophobicity Test
[0038] The controlled-release coated fertilizer products obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for hydrophobic angle and water vapor permeability. 100 mg of the prepared film material was ground into powder, and the static hydrophobic angle of the film material was tested using the sessile drop method; the water vapor permeability of the film material was tested by cutting the film material with uniform thickness and placing it on a wide-mouth bottle containing 30 mL of distilled water as a bottle cap and sealing the mouth, placing the sealed wide-mouth bottle in a drying dish with 1 L of concentrated sulfuric acid at the bottom for testing, and taking out the wide-mouth bottle every day to measure and record the mass. The experimental temperature was room temperature, and the data are shown in Table 2:
[0039] Table 2 Comparison of hydrophobic properties of materials
[0040]
[0041] As can be seen from Table 2, the hydrophobic angle of the coating material prepared according to the ratio of Examples 1 to 3 (based on mass ratio, ethyl cellulose: triethyl citrate: nano-titanium oxide = 20:2:1) is the largest compared to Comparative Examples 1 to 3, and the water vapor permeability is the smallest, indicating that the hydrophobic performance of the membrane material is the most excellent under the ratio of Examples 1 to 3.
[0042] Test Example 3: Controlled Release Experiment
[0043] The controlled-release coated fertilizer products obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to nutrient release experiments in accordance with "HG / T4216-2011 Rapid Detection Method for Nutrient Release Period and Release Rate of Slow-Release / Controlled-Release Fertilizers". The results are shown in Table 3.
[0044] Table 3 Comparison of controlled release performance
[0045]
[0046] From the data in the table, it can be seen that compared with comparative examples 1 to 3, Example 3 has the lowest initial dissolution rate and differential dissolution rate, and the longest controlled release period. It can be seen that the controlled release performance of the controlled release fertilizer coated fertilizer prepared in Example 3 is effectively improved.
[0047] The material of the present invention achieves a balance between strength and toughness by blending ethyl cellulose, triethyl citrate and nano titanium dioxide. In the experimental process of hydrophobicity test, the coating material prepared according to the ratio of Example 3 has the best hydrophobicity and the smallest water vapor permeability compared with Comparative Examples 1 to 3, which is conducive to the delayed release of nutrients by the coated controlled-release fertilizer; in the release rate experiment, the fertilizer in Example 3 of the present invention (the coating material in the controlled-release coated fertilizer accounts for 10% of the weight of the fertilizer core particles) has excellent performance in the initial nutrient release rate, differential dissolution rate and controlled release time, and the nutrient release period is 17 days, which has a longer controlled release time than other similar controlled-release fertilizers using ethyl cellulose as raw materials.
[0048] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A modified ethyl cellulose emulsion, characterized in that: In parts by mass, it includes 10-30 parts of ethyl cellulose, 50-150 parts of ethanol, 1-5 parts of triethyl citrate and 0.5-1.5 parts of nano-titanium dioxide, wherein the mass ratio of triethyl citrate to ethyl cellulose is not less than 10%, and the mass ratio of nano-titanium dioxide to ethyl cellulose is not more than 10%.
2. The modified ethyl cellulose emulsion according to claim 1, characterized in that: According to the mass ratio, the emulsion is composed of 60g of ethyl cellulose, 300g of anhydrous ethanol, 6g of triethyl citrate, and 15g of nano-titanium oxide ethanol dispersion, of which the nano-titanium oxide is 3g.
3. The modified ethyl cellulose emulsion according to claim 1, characterized in that: The ethyl cellulose contains 44.0%-51.0% ethoxyl group (-OC2H5) and has a viscosity of 7-10cp. The metal oxide is titanium oxide, the average particle size of the nano-titanium oxide ethanol dispersion is 15nm, and the titanium dioxide content is ≥20wt.%.
4. The method for preparing the modified ethyl cellulose emulsion according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: placing ethyl cellulose, ethanol, triethyl citrate and nano-titanium dioxide ethanol dispersion in a reaction container, stirring and mixing at 65-75° C. to obtain a modified ethyl cellulose emulsion product.
5. Use of the modified ethyl cellulose emulsion according to any one of claims 1 to 3 in the preparation of biodegradable controlled-release coated fertilizers.
6. The use according to claim 5, characterized in that: Pour the fertilizer core particles into a fluidized bed and preheat at 42-45°C, add modified ethyl cellulose emulsion into a peristaltic pump, and spray the modified ethyl cellulose emulsion onto the surface of the fertilizer core particles; After spraying, the product is solidified, dried and cooled to obtain the coated controlled-release fertilizer, the mass of the modified ethyl cellulose emulsion film layer is 1-15% of the mass of the fertilizer core particles, and the particle size of the controlled-release coated fertilizer core is 3-6 mm.
7. The use according to claim 6, characterized in that: The fertilizer core particles are urea particles, potassium chloride particles or compound fertilizer particles. The preheating time is 15 minutes, the speed of the peristaltic pump is 3-6 rpm, and the spraying pressure is set to 0.2-0.4 MPa.
8. The use according to claim 6, characterized in that: Before spraying the modified ethylcellulose emulsion, the steps of screening and dust removal of the fertilizer core particles are also included to ensure the uniformity and quality of the coated fertilizer.
9. The use according to claim 6, characterized in that: The curing and drying process adopts a gradually increasing temperature to promote cross-linking and curing of the emulsion, thereby further enhancing the controlled release effect of the coated fertilizer.